Implementing practices for the Chinese Nationalized Piano teaching model in undergraduate music education - Zou, Weixin; Hin-on, Tharanat; Sapaso, Pongpitthaya (Cogent education, 2024)
Chinese piano music has evolved into a unique expression of cultural identity, incorporating national elements that define its artistic image and emotional depth. The research objective is to investigate and analyze the implementation practices associated with the Chinese Nationalized Piano teaching model in undergraduate music education. The material and methods involve a comprehensive investigation, including surveys on the nationalized curriculum for piano education and the application of Chinese piano works, alongside interviews and analysis of teaching practices. The research results highlight the intricate ties between Chinese piano work and national themes, imagery, events, and emotions while revealing challenges such as weak awareness of piano nationalization teaching and limited student acceptance of ethnic music learning. The discussion emphasizes the importance of aligning educational objectives with cultural preservation goals and proposes curriculum reforms and teacher training recommendations. In conclusion, the study underscores the need for innovative approaches to effectively integrate national elements into music education and promote the development and appreciation of Chinese piano art within a national cultural context.